MASCULINITY OF PRABU SILIWANGI IN TRADITIONAL SUNDANESE BALLAD TEXTS (MASKULINITAS PRABU SILIWANGI DALAM TEKS KIDUNG TRADISIONAL SUNDA) - Resti Nurfaidah; Sarip Hidayat; Gunari Putra Erisman; Ilham Purwa Fauji (Jurnal Gramatika, 2023)
Why is Siliwangi so popular in Sundanese culture? He it is also enshrined in various place names, streets, foundations, and public organizations, and even has his own followers and oral-literary texts. Why is the concept of leadership, especially in Sundanese culture, always addressed to Siliwangi. This research is focused on the oral literature with the theme of Prabu Siliwangi's leadership in Ciamis Regency, as one of the research loci that has deep traces in the history of the Padjadjaran Kingdom. Some of the relics of royal rulers can be seen in that place, both memorials and oral works of literature that mention Padjadjaran and Prabu Siliwangi in the area. This research is a qualitative descriptive study using Beynon's masculinity concept approach to the figure of King Siliwangi. The method used in this study includes data collection that is determining the text of the kidung found in Ciamis Regency that contains the concept of leadership; data processing by decoding and determining the concept of Siliwangi's leadership in the text; and compiling data in the form of writing research results into scientific work. Based on Beynon's criteria, the results showed that Prabu Siliwangi had masculinity-forming factors that made him so strong and could fulfill the ideals, both as a man and a leader.